Exploring the importance of inter-departmental women's friendship in geography as resistance in the neoliberal academy. Issue 1 (2nd January 2019) - Webster, Natasha; Boyd, Meighan
ABSTRACT: Friendship has potential as a key coping and self-care strategy among early career researchers (ECR's) and has been shown to be crucial to overall well-being and sense of belonging, but its importance as a response to career pressures is not well studied. For ECR's, friendships within the university are situated in a specific structural and institutional context, and formigrant women, this includes an additional aspect of gendered complexity. At the same time friendships may prove difficult as heightened neoliberal metrics emphasize competition forfunding, positions and teaching requirements. Using autoethnographic intra-reflections on the authors' own friendship, bridging human geography and physical geography, this paper examines friendship of two ECR women from a homosocial perspective where institutional hierarchies and structures may be somewhat equalized. Drawing on the exploration of the authors' friendship during their PhD years and into their post-doc positions, we reflect on the importance of friendship as an act of support, self-care and resistance. We argue for heightening importance for examining the way friendship creates safe social spaces and offer new insights into the importance of friendships in career paths. Friendship in the neoliberal academy has transformative potential for creating a culture of well-being in geography.